Revocation of the Voting Rights of Persons with Disabilities who are Mentally Impaired - Umar, Risnawati Moh (CV. Rayyan Dwi Bharata, 2024)
Disability is developmental or developmental. Disability is characterized by significant limitations in intellectual functioning and adaptability. Children with developmental disabilities are children whose intellectual and cognitive abilities are below average. Such conditions can occur when the baby is in the womb or during childbirth, and can also occur in babies after birth. Many parties have revoked the right to vote for disabled people because the reason is that they are not considered